Islamic Religious Education Teachers' Efforts to Adapt to Digital Challenges - Sholahudin Muhammad Iqbal; Mohamad Ali (Tadrib: Jurnal Pendidikan Agama Islam, 2026)
The current digital era has had a significant impact on the education sector, where Islamic Religious Education (PAI) teachers are required not only to master religious material but also to be able to adapt technology in the learning process. The purpose of this study is to examine in depth the efforts of PAI teachers in adapting to digitalization, including adjusting learning methods, utilizing technology, and pedagogical approaches to meet the demands of the times. The research method used is a qualitative approach. Primary data sources were obtained through in-depth interviews with PAI teachers at SMK BATIK 1 Surakarta, while secondary data were obtained through literature studies from relevant books and scientific journals. Data analysis techniques were carried out through an interactive model that includes data reduction, data presentation, and drawing conclusions. The results and discussion indicate that the main challenges in PAI learning in the digital era include the gap in technology access, low digital literacy of educators, and the tendency of students to be more interested in entertainment content than educational materials. As a solution and adaptation effort, PAI teachers at SMK BATIK 1 Surakarta implemented a creative strategy by providing game-based quizzes to increase student motivation and active involvement. Furthermore, platforms such as blogs, digital journals, and video and infographic-based assignments are being utilized to instill Islamic values contextually. The success of this adaptation depends heavily on the synergy between teacher   creativity at school and parental supervision at home, creating a digital education ecosystem that is both character-based and religious